Răspuns :
[tex] \frac{1}{2} \div ( \frac{1}{3} \div \frac{1}{6} ) = \frac{1}{2} \div ( \frac{1}{3} \times 6) = \frac{1}{2} \div 2 = \frac{1}{2} \times \frac{1}{2} = \frac{1}{4} [/tex]
[tex] \frac{1}{2} \div ( \frac{1}{3} + \frac{1}{6} ) = \frac{1}{2} \div ( \frac{2}{6} + \frac{1}{6} ) = \frac{1}{2} \div \frac{3}{6} = \frac{1}{2} \times \frac{6}{3} = \frac{1}{2} \times 2 = 1[/tex]
[tex] \frac{1}{2} \div ( \frac{1}{3} + \frac{1}{6} ) = \frac{1}{2} \div ( \frac{2}{6} + \frac{1}{6} ) = \frac{1}{2} \div \frac{3}{6} = \frac{1}{2} \times \frac{6}{3} = \frac{1}{2} \times 2 = 1[/tex]
1/2:(1/3x6/1)-se simplifica 3 și 6
1/2x1/2=1/4
1/2:(1/3+1/6)-se amplifica 1/3 cu 2
1/2:(2/6+1/6)
1/2x6/3-se simplific 6 cu 3
1/2x2/1- se simplifica 2 cu 2
=1
1/2x1/2=1/4
1/2:(1/3+1/6)-se amplifica 1/3 cu 2
1/2:(2/6+1/6)
1/2x6/3-se simplific 6 cu 3
1/2x2/1- se simplifica 2 cu 2
=1